LITERATURE REVIEW OF ISLAMIC SOCIAL FINANCE CONTRIBUTION IN INDONESIA - Muhammad Rizal Hasibuan; Marliyah Marliyah (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2023)
This study aims to review and map the concepts and principles of Islamic social finance in their contribution to the Indonesian economy, using qualitative methods with content analysis sourced from articles on the Google Scholar database. Data was obtained using the Publish or Perish (PoP) application for a period of 10 years (2012-2022) with the keywords concepts and principles of Islamic social finance, accessed on January 7 2023, 53 articles (population) were obtained and 20 articles were taken as samples, while data analysed 15 articles. The results of the study found that the most discussed themes were 1) Development of Islamic Social Finance with 5 articles (33%), Islamic Accounting with 3 articles (20%), Disclosure of Islamic Social Reporting with 3 articles (20%), Development of Microeconomics with 2 articles (13%) Performance of Islamic Social Finance (Public) 2 articles (13%). The concept of Islamic social finance recommended by the article in overcoming economic problems in Indonesia, among others; (1) Distribution of BLT originates from zakat, infaq, or alms; (2) Increasing waqf with cash waqf and productive waqf schemes; (3) Business capital assistance to Micro, Small and Medium Enterprises (UMKM); (4) Providing business capital with a qardhul hasan loan scheme; (5) Providing an understanding of Islamic economic and financial literacy; (6) Technology development Keywords: Concept, Islamic economics, Islamic social finance